Modern optimization algorithms and applications in solar photovoltaic engineering - Tyukhov, I. (IGI Global, 2016)
This chapter is devoted to main tendencies of optimization in photovoltaic (PV) engineering showing the main trends in modern energy transition - the changes in the composition (structure) of primary energy supply, the gradual shift from a traditional (mainly based on fossil fuels) energy to a new stage based on renewable energy systems from history to current stage and to future. The concrete examples (case studies) of optimization PV systems in different concepts of using from power electronics (particularly maximum power point tracking optimization) to implementing geographic information system (GIS) are considered. The chapter shows the gradual shifting optimization from specific quite narrow areas to the new stages of optimization of the very complex energy systems (actually smart grids) based on photovoltaics and also other renewable energy sources and GIS. Â© 2016 by IGI Global. All rights reserved.